2012
DOI: 10.5194/acpd-12-18459-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional and monthly and clear-sky aerosol direct radiative effect (and forcing) derived from the GlobAEROSOL-AATSR satellite aerosol product

Abstract: Using the GlobAEROSOL-AATSR dataset, estimates of the instantaneous, clear-sky, direct aerosol radiative effect and radiative forcing have been produced for the year 2006. Aerosol Robotic Network sun-photometer measurements have been used to characterise the random and systematic error in the GlobAEROSOL product for 22 regions covering the globe. Representative aerosol properties for each region have been derived from the results of a wide range of literature sources and, along with the de-biased GlobAEROSOL A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Clear‐sky global‐mean estimates of the shortwave (SW) aerosol DRE at the top of atmosphere (TOA) range between −2 and −7 W m −2 (e.g., Boucher et al., 2013; Christopher & Zhang, 2002; Henderson et al., 2013; Matus et al., 2019, 2015; Myhre et al., 2007; Reddy et al., 2005; Remer & Kaufman, 2006; Thomas et al., 2013; Yu et al., 2006; T. X.‐P. Zhao et al., 2011; T. X. Zhao et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Clear‐sky global‐mean estimates of the shortwave (SW) aerosol DRE at the top of atmosphere (TOA) range between −2 and −7 W m −2 (e.g., Boucher et al., 2013; Christopher & Zhang, 2002; Henderson et al., 2013; Matus et al., 2019, 2015; Myhre et al., 2007; Reddy et al., 2005; Remer & Kaufman, 2006; Thomas et al., 2013; Yu et al., 2006; T. X.‐P. Zhao et al., 2011; T. X. Zhao et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of aerosols on climate were traditionally made by using chemical transport models (CTM) or global climate models (GCM), or their regional versions. In the last decade satellite observations have increasingly been used to provide observation-based estimates of the effects of aerosols on climate (Yu et al, 2006;Thomas et al, 2012). Satellite observations offer the advantage of large spatial coverage with the same instrument and technique as implemented in an instrument-specific retrieval algorithm, at the cost of accuracy and temporal coverage offered by most ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, considerable effort has been done in order to quantify the magnitude of the aerosol direct radiative effects considering clear-sky situations (Zhao et al, 2011;Nikitidou et al, 2014) or all-sky situations (Myhre et al, 2007Chand et al, 2009;Heald et al, 2014;Oh et al, 2014) and also to investigate the indirect effects of the aerosols on the solar radiation (Rap et al, 2013). For example, based on the Monitoring Atmospheric Composition and Climate re-analysis aerosol data, Bellouin et al (2013) estimated the global aerosol direct radiative effects at the surface in clear-sky situations to be −10.8 ± 1.9 W m −2 , while Thomas et al (2012) reported −12 ± 6 W m −2 using GlobAEROSOL-AATSR satellite aerosol products. Yu et al (2006) calculated the clear-sky aerosol direct effects separately for land and ocean surfaces quantifying them to be −11.8 ± 1.9 and −8.8 ± 0.7 W m −2 , respectively; the best estimates of Bellouin et al (2013) are −11.5 ± 1.9 W m −2 for land and −10.6 ± 1.9 W m −2 for ocean.…”
Section: Introductionmentioning
confidence: 99%